Protective effect of heme oxygenase‐1 on hepatic ischemia‐reperfusion injury through inhibition of platelet adhesion to the sinusoids. Issue 4 (25th March 2013) - Tamura, Takafumi; Kondo, Tadashi; Ogawa, Koichi; Fukunaga, Kiyoshi; Ohkohchi, Nobuhiro
Abstract Background and Aim Heme oxygenase‐1 (HO‐1) acts as a protector against hepatic inflammatory injury. HO‐1 catalyzes the conversion of heme protein to biliverdin, free iron, and carbon monoxide. Pro‐inflammatory responses play critical roles in hepatic ischemia‐reperfusion (I/R) injury, and carbon monoxide effectively downregulates I/R injury. The aim of this study was to evaluate the mechanism by which HO‐1 reduces warm I/R injury. Methods Sprague–Dawley rats were divided into two groups: the 20‐min ischemia group (control group; n = 6) and the 20‐min ischemia with cobalt protoporphyrin (CoPP group; n = 6). CoPP is an inducer of HO‐1 in the sinusoids. Kupffer cells were labeled using the liposome entrapment method, and platelets were labeled with rhodamine‐6G. The adherent platelets were observed for up to 120 min after reperfusion by intravital microscopy. Results In the control group, the number of adherent platelets significantly increased than in the CoPP group. Terminal deoxynucleotidyl transferase‐mediated dUTP nick end labeling‐positive cells were observed after 120 min of reperfusion in the control group. They were not observed in the CoPP group. In the CoPP group, serum alanine transaminase and interleukin‐6 levels reduced after reperfusion. Moreover, the flow velocity of platelets in the hepatic sinusoid markedly increased. Conclusions This study suggests that HO‐1 inhibits platelet adhesion to sinusoids. Such inhibition leads to the prevention of hepatic I/R injury.